Pain Management Strategies and Lessons from the Military: A Narrative Review - April Hazard Vallerand; Patricia Cosler; Jack E. Henningfield; Pam Galassini (Pain Research and Management)
BACKGROUND: Wounded soldiers often experience substantial pain, which must be addressed before returning to active duty or civilian life. The United States (US) military has instituted several guidelines and initiatives aimed at improving pain management by providing rapid access to medical care, and developing interdisciplinary multimodal pain management strategies based on outcomes observed both in combat and hospital settings.